Kebijakan Kriminal Terhadap Tindak Pidana Pencabulan Yang Dilakukan Oleh Anak Di Wilayah Pancur Batu - Rosalyna Damayanti Gultom; Alvi Syahrin; Edi Yunara; Marlina Marlina (Universitas Sumatera Utara, 2019)
Abstract. Children as successors to the baton of the struggle of the nation and state actually grasp the hopes of the nation. The good and bad future of the nation depends also on the good and bad conditions of the child at this time. However, now children often fall into various crimes, including the crime of sexual abuse. Crimes of sexual immorality can not only be done by adults, but children also tend to easily fall into it. There are 8 (eight) cases of sexual offenses committed by children in the Pancur Batu area that occurred in 2016 to 2017. The problems raised in the writing of this thesis are how to regulate criminal acts of sexual abuse committed by children in the legislation in Indonesia, then what are the factors that cause criminal acts of sexual abuse committed by children in the Pancur Batu area, and how is the criminal policy in handling criminal acts of sexual abuse committed by children in the Pancur Batu area. Keywords : Criminal Policy, Abuse done by Children